2021
DOI: 10.1590/1678-7757-2020-1079
|View full text |Cite
|
Sign up to set email alerts
|

Multi-state outcome analysis of treatment interventions after failure of non-surgical root canal treatment: a 13-year retrospective study

Abstract: Multi-state outcome analysis of treatment interventions after failure of non-surgical root canal treatment: a 13-year retrospective study Objective: To examine the factors affecting the transitions through treatment interventions after failure of non-surgical root canal treatment (NS-RCT). Methodology: Insurance enrollment and claim information for enrollees of Delta Dental of Wisconsin (DDWI), USA were analyzed for 438,487 initial NS-RCT procedures to determine the effect of initial provider type and other co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Diabetes mellitus has been shown in a systematic review of longitudinal studies to be associated with a lower tooth survival after root canal treatment (Cabanillas-Balsera et al, 2019;Mindiola, 2006;Ng et al, 2011b;Wang et al, 2011). Coronary artery disease has been studied as a factor affecting tooth extraction after root canal treatment, though in a multivariable analysis, there was no association with tooth extraction (Wang et al, 2011).…”
Section: Systemic Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes mellitus has been shown in a systematic review of longitudinal studies to be associated with a lower tooth survival after root canal treatment (Cabanillas-Balsera et al, 2019;Mindiola, 2006;Ng et al, 2011b;Wang et al, 2011). Coronary artery disease has been studied as a factor affecting tooth extraction after root canal treatment, though in a multivariable analysis, there was no association with tooth extraction (Wang et al, 2011).…”
Section: Systemic Healthmentioning
confidence: 99%
“…It needs to be stressed that the present narrative review focuses on tooth survival in the sense that the tooth has not been extracted. There is also the possibility to study the survival of the endodontic treatment, in other words, untoward events or that any further treatment of the endodontic conditions such as extraction, retreatment or endodontic surgery has been performed (Bhagavatula et al, 2021; Chen et al, 2008; Dawson et al, 2017; Lumley et al, 2008; Raedel et al, 2015b). As survival of the endodontic treatment includes extractions, reports of survival of the endodontic treatment will be inferior to survival of the tooth.…”
Section: Reviewmentioning
confidence: 99%
“…Recently, a North American study based on insurance data reported extraction of 14% of teeth during a follow‐up period of 14 years. However, survival curves revealed a cumulative hazard greater than 0.4 after 10 years, though with very broad confidence intervals (CI) (Bhagavatula et al, 2021). In another cohort from the same North American database, the 6‐year retention rate was 88% (Haxhia et al, 2021).…”
Section: Introductionmentioning
confidence: 99%